Charge transport effect and photovoltaic conversion of two-dimensional CdSeS quantum dot monolayers in inverted polymer solar cells. Issue 38 (16th September 2019) - Lim, Guh-Hwan; Lee, Kyu Seung; Park, Young Jae; Shim, Jaeho; Choi, Jin Woo; Kim, Minju; Jin, Yeonghoon; Lim, Byungkwon; Yi, Yeonjin; Lee, Chang-Lyoul; Hwang, Jun Yeon; Son, Dong Ick
Abstract : Herein, we demonstrate that two-dimensional (2D) CdSeS quantum dot monolayers (QDM) can strongly influence efficient charge transport and charge separation, improving the performance of inverted polymer solar cells (iPSCs). Abstract : Herein, we demonstrate that two-dimensional (2D) CdSeS quantum dot monolayers (QDM) can strongly influence efficient charge transport and charge separation, improving the performance of inverted polymer solar cells (iPSCs). Also, for the first time we report the electronic band structure of CdSeS and CdSeS@ZnS QDs and an effective approach to apply the 2D QDM as an effective electron transport layer in iPSCs from work function studies. The iPSCs with the 2D CdSeS QDM showed maximum power conversion efficiencies of 8.83%, which were 26% higher than the reference. Ultraviolet photoelectron spectroscopy and time-correlated single photon counting (TCSPC) measurements were performed to confirm the charge separation and electron transport behavior in the iPSCs with 2D QDMs. The PL decay time of the iPSCs with the CdSeS QDM at 720 nm was ∼60 ps, which is much faster than that of the iPSCs without the 2D QDM. The enhanced photovoltaic performance of the iPSCs with the 2D CdSeS QDM can be attributed to the effective charge separation and electron transport performance due to the high built-in voltage and fast exciton decay time from the 2D QDM.